2011
DOI: 10.1016/j.visres.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Similar neural adaptation mechanisms underlying face gender and tilt aftereffects

Abstract: Visual aftereffects have been found for a wide variety of stimuli, ranging from oriented lines to human faces, but previous results suggested that face aftereffects were qualitatively different from orientation (tilt) aftereffects. Using computational models, we predicted that these differences were due to the limited range of faces used in previous studies. Here we report psychophysical results verifying this prediction. We used the same paradigm to test tilt aftereffects (TAE) and face gender aftereffects (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 31 publications
11
63
2
Order By: Relevance
“…The face stimulus was based on an average female face used in Zhao et al (2011). A line rendering of this face, composed of 36 individual short segments, was created manually in Inkscape (version 0.48.2) using the bezier curve tool.…”
Section: Methodsmentioning
confidence: 99%
“…The face stimulus was based on an average female face used in Zhao et al (2011). A line rendering of this face, composed of 36 individual short segments, was created manually in Inkscape (version 0.48.2) using the bezier curve tool.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, locations in face space might be encoded by multiple channels, each relatively narrowly-tuned to a sub-region of face space, analogous to the channels thought to underlie the perception of orientation (Giese & Leopold, 2005;Robbins et al, 2007;Ross, Deroche, & Palmeri, 2013;Wallis, 2013;Webster & MacLeod, 2011;Zhao, Seriès, Hancock, & Bednar, 2011). According to this proposal, any dimension of facial variance is encoded by many channels, each responding maximally to some particular value along the dimension and less to values 'higher' or 'lower' than it, with the average face having no unique status.…”
Section: Local Repulsion or Renormalisation In Face Space?mentioning
confidence: 99%
“…It has been suggested that shifts in neutral category boundaries can differentiate locally repulsive from renormalising aftereffects if one compares the magnitudes of shifts induced by different 'strengths' of adaptor (Burton, Jeffery, Skinner, Benton, & Rhodes, 2013;Jeffery et al, 2010Jeffery et al, , 2011McKone et al, 2014;Pond et al, 2013;Skinner & Benton, 2010, 2012Zhao et al, 2011). A continuum of facial images morphing between different genders (for example) can be thought of as a one-dimensional slice through an artificial face space.…”
Section: Evidence From Aftereffects For Norm-based Representation Of mentioning
confidence: 99%
See 2 more Smart Citations